Green Value Stream Mapping: A Tool For Increasing Green Productivity (The Case of PT. NIC) - Raymond Budihardjo; Wijanto Hadipuro (Soegijapranata Catholic University, 2022)
The role of the environment in business success is increasing from day to day. One of the ways to harmonize the goals of making a profit with the environment is by achieving green productivity. Green productivity means that companies can increase their productivity and at the same time improve their environmental performance. To reach that goal one of the ways is that businesses apply value stream mapping and make all the activities to be green which is known as a Green Value Stream Mapping. A combination of secondary data collection and Focus Group Discussions involving all relevant production staffs was conducted to get the initial data and the ideas to improve the performance of electricity, LPG, and water consumption at PT NIC Semarang. Compared to the initial data of the Current State Green Value Stream Mapping, the improvements resulted from the Future State Green Value Stream Mapping were a 51.4% decrease in electricity consumption, a 24.42% decrease in LPG consumption, and a 60% decrease in water consumption. From this empirical study, two important outcomes of future implications were found. For the food industry, implementing GVSM should be adjusted in such a way that the experiments to reach the Future State Green Value Stream Mapping will not affect the quality of the final products and that FGDs are very effective to generate ideas of improvements and getting commitments from production staffs to implement the improvements